CLAY MINERALOGY OF THE SEDIMENTARY IRON-NICKEL ORE OF AGIOS IOANNIS, NE BOEOTIA: NEW DATA AND IMPLICATION FOR DIAGENETIC MODIFICATIONS Christidis G. - Christidis, G.E.; Skarpelis, N. (Bulletin of the Geological Society of Greece, 2010)
The clay mineralogy of the sedimentary Fe-Ni deposit of Agios Ioannis and a Ni lateritic profile from Pavlos, both in Lokris area, Greece, is investigated. The clay fraction of samples from Agios Ioannis consists mainly of Fe-rich chlorite and Fe-smectite, with minor serpentine, hematite and goethite. Locally, disordered talc (kerolite and/or pimelite), illite, R1 mixed layer illite/smectite and gibbsite are identified. The lateritic profile has different composition and contains mainly Fe-rich smectite (nontronite and/or ferruginous montmorillonite) with minor serpentine, goethite, magnetite, and talc, whereas chlorite is absent. It is suggested that in the Agios Ioannis deposit chlorite has formed from smectite via R0 mixed layer chlorite/smectite with >80% chlorite layers. The source of Al is probably the diagenetic transformation of pedogenic goethite to hematite during burial. The lack of chlorite in the lateritic profile of Pavlos is attributed to the limited presence of goethite. Smectite is believed to be a major mineralogical constituent of the Fe-Ni ores of the broader Lokris area.